2021
DOI: 10.3390/jcm10132797
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for Perioperative Blood Transfusion in Patients Undergoing Open Cystectomy and Urinary Diversion and Development of a Nomogram: An Observational Cohort Study

Abstract: Open radical cystectomy is associated with a substantial rate of perioperative blood transfusion. Early detection of potentially modifiable perioperative factors could reduce the need for perioperative blood transfusion and thus positively impact the outcome. We conducted an observational, single-center cohort study of 1168 patients undergoing cystectomy. Perioperative blood transfusion was defined as the need for packed red blood cells and/or fresh frozen plasma units within the first 24 h after the initiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
3
2
0
Order By: Relevance
“…Female patients were more likely to require PBT in our series, which is consistent also with other cystectomy series [7,17]. This likely reflects anatomic differences.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Female patients were more likely to require PBT in our series, which is consistent also with other cystectomy series [7,17]. This likely reflects anatomic differences.…”
Section: Discussionsupporting
confidence: 90%
“…This likely reflects anatomic differences. Advanced age is also a reproducible risk factor for needing PBT, as shown in our series and other reports [17]. All cases were performed in an open fashion in this series, but an increasing proportion of RC is being performed robotically today.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Recently, there has been increasing interest in the role of anaemic status as a prognostic factor in surgical outcomes after RC. High circulating oxygen transport capacity has higher impact compared to other factors like duration of surgery, tumour stage, or oral anticoagulation for incidence of perioperative blood transfusion (PBT) [ 28 ]. A study by Pavone et al [ 29 ] showed that preoperative anaemia condition is very common in patients with MIBC and is proved to be a predictor of postoperative complications, but not of 90-day mortality.…”
Section: Resultsmentioning
confidence: 99%
“…Expectedly, preoperative anemia can be associated with increased PBT. 98 , 99 Thus, the effects of preoperative anemia on clinical outcomes have not been clearly delineated from those of PBT. Nevertheless, the correction of anemia, as highlighted in the 2013 ERAS guidelines, is an important component of medical optimization prior to surgery.…”
Section: Targeted Components Of Erasmentioning
confidence: 99%